Особливості голоценових грунтів в межах захисного валу Журжинецького городища на Черкащині - Матвіїшина, Ж. М.; Пархоменко, О. Г. (Київський національний університет імені Тараса Шевченка, 2017)
Особливості давніх та сучасних (фонових) ґрунтів в межах захисного валу Журжинецького городища були досліджені за допомогою палеопедологічного методу з використанням геоархеологічного підходу. Це дозволило визначити типи ґрунтів (включаючи грунт раннього залізного віку і тренди кліматичних змін від раннього залізного віку до сучасності). Профіль фонового ґрунту визначено як сірий опідзолений грунт, а ґрунту раннього залізного віку під насипом валу як лісовий чорнозем. Умови проживання людини з 2600 ВР змінилися від сухіших степових помірного клімату до більш вологих і прохолодніших (сірі лісові ґрунти) лісостепу.

According to invitation of scientific worker of archaeological inspection of Cherkassy regional state administration office culture O. Nazarov we studied soils under protective bank of Zhurzhynetsk settlement. The aim of the study were: to determined the buried under protective bank soil; according possibility, to reconstruct human habitation nature conditions of the last; to set the trends of climate changes from Early Iron Age to the present. Researched bank have height to 2,5 m. Investigation provided for macromorphological analysis of soils profiles, drawings and conclusions about types of soils as reflecting of last paleolanscapes. Soils were studied in the two clearings (sites): clearing №1 lies inside bank, were studied soils on the top of bank and baried soil of Early Iron Age recovered by the embankment. Background modern soil was researched in the clearing №2. Stratigraphy composition defines the next changing layers and soils from top to the bottom of bank: – chernozem (possible forest) to 0,85 m with a clear Pk. It overlaps redeposit layer of loess (0,2 m); – loess material of embankment (0,85 m-2,3 m) on top is almost “clean (poor)” loess with Pk of modern soil, inside interval 1,5-2,3 m – alternating of losses layers and fragments of soil sod; – ash layer on the surface of the buried soil; – baried soil of Early Iron Age – podzolic chernozem, possible typical chernozem (2,3-3,5 m); – bed rock – Bug loess (3,3-3,5 m) – this species takes part in the embankment formation. Background modern soil have genetic horizon HE, Ihp, Iepk, Pik, Pk which are inherited to the gray podzolic forest soils. Conclusion. Compare of Early Iron Age (2600 BP) buried soil with back ground modern one allows to make a conclusion, that in ancient time formed the soil, closed to typical one weakly podzolic chernozem, but background modern soil are presented by typical gray podzolic forest soil. Characteristics of Early Iron Age soil indicates on its formation under conditions of warm-temperate climate of the southern forest-steppe with of the existence of wide open space areas with domination of steppe canoes. The soil on the top of the bank is closed to chernozems, but probably partly formed under forest cover (the forest chernozem of steppe after A. Travleev), its material probably was partly redeposited. The proximity of the buried (Early Iron Age time) soil to the podzolic or typical chernozem in compare with background modern forest podzolic soil indicates on changing of physical-geographical and climatic conditions in the direction of modernity to side of wetter and, maybe, more cool warm temperate climate. Buried as well as background modern soil can be form within the same nature zone, but the described background one is a formation comparing with more northern area. Consequently, in the Early Iron Age the territory was occupied by the wide areas of steppe landscape. Modern gray podzolic soil was formed under forest, i.e. the amount of precipitation increased comparing with the Early Iron Age and climatic conditions in ancient time were drier than in contemporary ones. A profile soil detects features of similarities to the forest soil though now the forest is preserved only in depressions, in ravines and gullies. Perhaps, the process of forest reduction is associated with modern human activity.
Peculiarities of Holocene soils development inside the boundaries of the protective bank of Zhurzhynets settlement of Cherkaschyna
Keywords: грунт; педогенез; голоцен; геоархеологічний підхід; soil; pedogenesis; Holocene; geo-archaeological approach